Analisis Kemampuan dan Kemauan (ATP dan WTP) Penumpang Angkutan Kota Trans Jogja Jalur 5a - Vera Pramudyasari; Ircham; Herna Puji Astutik (Retii, 2023)
Trans Jogja is expected to improve the existing urban transportation system in the Yogyakarta area, so as to create safe, comfortable and timely urban public transportation, especially Trans Jogja route 5A where this route is a route that passes through work centers, shopping centers and campuses so that the quality of service must be improved. to the wider community. Primary data was obtained by providing questionnaires for Trans Jogja Line 5A users. Secondary data is obtained from BPS (Central Static Agency) Yogyakarta Province which then the data is analyzed. Results of data analysis to determine the ability (ATP) and willingness (WTP) to pay Trans Jogja fares. From the results of the analysis of the ability of Trans Jogja Line 5A passengers based on questionnaires distributed to 100 respondents, from the results of surveys and calculations that have been carried out for ATP amounting to Rp. 5,763.46. The amount of value (WTP) is IDR 3,060 from the results obtained by the higher level of community ability.